Confessing history : explorations in Christian faith and the historian's vocation - Fea, John; Green, Jay (Jay D.); Miller, Eric, 1966- (University of Notre Dame Press, 2010)
The contributors to Confessing History ask how the vocation of historian affects those who are also followers of Christ. What implications do Christian faith and practice have for living out one's calling as an historian? And to what extent does one's calling as a Christian disciple speak to the nature, quality, or goals of one's work as scholar, teacher, adviser, writer, community member, or social commentator? Written from several different theological and professional points of view, the essays collected in this volume explore the vocation of the historian and its place in both the personal and professional lives of Christian disciples. --From publisher's description.